The effect of perceived organizational support and organizational commitment on turnover intention: Mediated by job satisfaction - Dany Dzakwan Likardo; Praningrum Praningrum (Jurnal Fokus Manajemen Bisnis, 2025)
Turnover intention is a serious challenge for companies to maintain quality human resources to help the company continue to achieve its goals. In analyzing turnover intention behavior, researchers formulate factors that include perceived organizational support, organizational commitment, and job satisfaction. This study uses the role of job satisfaction as a mediator to analyze the effect between perceived organizational support and organizational commitment on employee turnover intention. This study uses a quantitative approach and stratified random sample technique, the sample amounted to 165 employees of Narendra Dewa Yoga Company in Bengkulu City. Using Smart PLS version 4 software, the structural equation modeling  partial least square technique was used to analyze the data. The findings state that perceived organizational support, organizational commitment, and job satisfaction negatively and significantly affect turnover intention. Perceived organizational support and organizational commitment positively and significantly affect job satisfaction. Job satisfaction can mediate the effect of perceived organizational support and organizational commitment on turnover intention. Therefore, companies can improve their practices by paying more attention to employees through programs that support employee welfare, recognition, and contribution. The company also needs to consider aspects that can enhance employee job satisfaction and create a more harmonious work atmosphere to foster employee loyalty and prevent turnover.